Temporal synchrony is an effective cue for grouping and segmentation in the absence of form cues - Rideaux, Reuben; Badcock, David R.; Johnston, Alan; Edwards, Mark (Association for Research in Vision and Ophthalmology, 2016)
The synchronous change of a feature across multiple discrete elements, i.e., temporal synchrony, has been shown to be a powerful cue for grouping and segmentation. This has been demonstrated with both static and dynamic stimuli for a range of tasks. However, in addition to temporal synchrony, stimuli in previous research have included other cues which can also facilitate grouping and segmentation, such as good continuation and coherent spatial configuration. To evaluate the effectiveness of temporal synchrony for grouping and segmentation in isolation, here we measure signal detection thresholds using a global-Gabor stimulus in the presence/absence of a synchronous event. We also examine the impact of the spatial proximity of the to-begrouped elements on the effectiveness of temporal synchrony, and the duration for which elements are bound together following a synchronous event in the absence of further segmentation cues. The results show that temporal synchrony (in isolation) is an effective cue for grouping local elements together to extract a global signal. Further, we find that the effectiveness of temporal synchrony as a cue for segmentation is modulated by the spatial proximity of signal elements. Finally, we demonstrate that following a synchronous event, elements are perceptually bound together for an average duration of 200 ms.